Lineas umbrasque facere ausi sumus. Gellius, Chalcidius and Plato's translation - Delle Donne, Carlo (Ciceroniana On Line, 2023)
The article focuses on two instances of Latin translations of Plato: a passage by Gellius relating to the Symposium; and a commentary on the Timaeus by Chalcidius. Notwithstanding the difference in culture and intent between the two authors, a basic analogy seems to emerge regarding the nature of translation and its conceptualisation: translating entails re-producing a model; but every reproduction is, as such, defective with respect to its paradigm: for this reason, the Latin rendering of Plato’s Greek may aspire, at most, to be an adequate, albeit inferior, transposition of it. In other words, the same model/copy device that pervades Platonic philosophy seems to apply to translation practice; the Platonic background of Gellius and Chalcidius thus seems to guide their way of conceiving translation from Greek into Latin.